Efficacy and safety of bimekizumab for the treatment of psoriasis: a systematic review and meta-analysis of randomized clinical trials - Yuanyuan Qiu; Yang Zhu; Yun Liu; Qiliang Liu (Taylor & Francis Group, 2023)
Aim This study aimed to evaluate the efficacy and safety of bimekizumab for psoriasis. Methods The PubMed, Web of Science, Cochrane Library, and Embase databases were systematically searched until November 20, 2022, to identify randomized controlled trials (RCTs) reporting the efficacy and safety of bimekizumab. The identified studies were screened according to inclusion and exclusion criteria, and a meta-analysis was performed on the selected studies using the Stata (version 17.0) software to investigate the efficacy and safety of bimekizumab. Results Six studies involving 1252 participants were considered. Compared with the control group which received placebo, the bimekizumab group had a larger number of patients with improvement in Psoriasis Area and Severity Index (PASI) of at least 75% (PASI75) (RR: 20.54, 95%CI: 12.41-33.99; p = .000), at least 90% (PASI90) (RR:16.99, 95%CI: 7.09-40.68; p = .000) and 100%(PASI100) (RR:14.57; 95%CI: 5.26-40.35; p = .000) and a larger number with improvement in Investigator Global Assessment (IGA) response (RR:22.57; 95%CI: 12.74-39.98; p = .000). There was no obvious difference between the bimekizumab and placebo groups in treatment of emergent adverse events (TEAEs) (RR:1.17; 95%CI: 0.93-1.47; p > .05) and serious TEAEs (RR: 0.67; 95%CI: 0.28-1.61; p > .05). Conclusions Bimekizumab shows promising efficacy for the treatment of psoriasis with favorable safety records.